1992
DOI: 10.1093/nar/20.23.6235
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation by folate: inducible gene expression inDictyosteliumtransformants during growth and early development

Abstract: The Dictyostelium discoidin genes are induced in bacteria-grown cells shortly before the onset of development but are also highly expressed during growth in axenic medium. We here show that axenically growing cells strongly respond to the extracellular signal folate by suppressing discoidin synthesis while cell growth and development is not substantially affected. Repression occurs via two previously identified promoter elements, the dIE and the dAXE. Removal of the signal molecules or setting cells up for dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 24 publications
2
57
0
Order By: Relevance
“…1B (see Materials and Methods for a description of the other constructs). Two independent constructs for homologous recombination were then linearized and transformed by electroporation into JH10 cells, a thymidine auxotroph (32,56 To further examine the possibility that ERK1 is essential for growth, we made an ERK1 antisense construct with the discoidin I-y (Discly) promoter, whose expression can be regulated by exogenous folate during vegetative growth (3,66). This gene is not expressed in cells grown on bacteria or in axenic culture when cells are maintained at a very low density (15,66).…”
Section: Multicellular Development In Dictyostelium Discoideum Ismentioning
confidence: 99%
See 2 more Smart Citations
“…1B (see Materials and Methods for a description of the other constructs). Two independent constructs for homologous recombination were then linearized and transformed by electroporation into JH10 cells, a thymidine auxotroph (32,56 To further examine the possibility that ERK1 is essential for growth, we made an ERK1 antisense construct with the discoidin I-y (Discly) promoter, whose expression can be regulated by exogenous folate during vegetative growth (3,66). This gene is not expressed in cells grown on bacteria or in axenic culture when cells are maintained at a very low density (15,66).…”
Section: Multicellular Development In Dictyostelium Discoideum Ismentioning
confidence: 99%
“…Expression of the promoter, however, can be repressed in axenic culture (even if the cells are at high density) by the addition of 1 mM folate (3). When the folate is removed, the Discly gene is then expressed (3).…”
Section: Multicellular Development In Dictyostelium Discoideum Ismentioning
confidence: 99%
See 1 more Smart Citation
“…However, these attempts failed, suggesting that rapA might be an essential gene in Dictyostelium. In the present study, we have expressed a rapA antisense construct under the control of the folate repressible discoidin promoter (Blusch et al, 1992) and have examined the effects of Rap1 depletion on cell function. We have also demonstrated that Rap1 is activated in response to hyperosmotic stress and low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Different sequence elements within the discoidin promoter were responsible for repression by CAMP and folate , respectively. Folate may be important in the development of Dictyostelium cells as a singal molecule for the presence of bacteria on which this organism feeds (89) .…”
Section: Eukaryotesmentioning
confidence: 99%